Design, optimization and evaluation of an ion-triggered in situ nasal gel of selegiline for antidepressant therapy - Antesh Kumar Jha; Shiv Kumar Srivastava; Mahesh Prasad; Shashi Shankar; Abhishek Kumar Singh (Journal of Applied Pharmaceutical Research, 2026)
Background: Oral delivery of selegiline is limited by extensive first-pass metabolism, low and variable bioavailability, and restricted brain access due to the blood–brain barrier. Intranasal drug delivery offers a non-invasive strategy for direct nose-to-brain transport. The present study aimed to design, optimize, and evaluate an ion-triggered in situ nasal gel of selegiline using sodium alginate and HPMC to potentiate brain delivery and antidepressant efficacy. Methodology: Preliminary screening was performed using the Plackett–Burman design to identify critical formulation variables. Further optimization was carried out using the Box–Behnken design with sodium alginate (0.5–2% w/v), HPMC (0.5–1% w/v), and CaCl₂ (10–50 mM) as independent variables. The optimized formulation was evaluated for physicochemical properties, rheology, gelation time, gel strength, mucoadhesive strength, in vitro and ex vivo drug release, histopathology, in vivo antidepressant activity, and stability. Results and Discussion: The optimized formulation (1.25% sodium alginate, 0.75% HPMC, 30 mM CaCl₂) exhibited suitable sol viscosity (~150 mPa·s), rapid gelation (~34 s), adequate gel strength (~350 g), and good mucoadhesive strength (~3140 dyne/cm²). Sustained drug release (~98% in 8 h in vitro; ~94% in 6 h ex vivo) was achieved. The formulation was non-irritant to nasal mucosa, showed enhanced antidepressant activity in vivo, and remained stable for 3 months under stability studies. Conclusion: The optimized sodium alginate–HPMC ion-triggered in situ nasal gel of selegiline offers a safe, stable, and effective nose-to-brain delivery system with sustained release and improved antidepressant activity, making it a promising alternative to oral therapy.